1995
DOI: 10.1111/j.1751-1097.1995.tb03963.x
|View full text |Cite
|
Sign up to set email alerts
|

CIRCADIAN RHYTHM OF Robinia pseudoacacia LEAFLET MOVEMENTS: ROLE OF CALCIUM AND PHYTOCHROME

Abstract: Abstract— The effect of external calcium level, calcium ionophore A23187 and red light on the circadian rhythm of Robinia pseudoacacia leaflet movements has been studied. Fifteen minute red light pulses shifted the phase of leaflet rhythmic movement with a phase‐response curve type 0. Maximum advances and delays (about 10 h and 8 h, respectively) were obtained between circadian time (CT) 10 and CT 12 at the end of a subjective day. An almost null effect was obtained at the end of a subjective night. Phytochrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 35 publications
1
17
1
Order By: Relevance
“…However in view of these data and the growing body of evidence that Ca 2ϩ plays an integral role in a number of rhythmic phenomena in plants (Neuhaus et al, 1993;Gomez and Simon, 1995;Anderson and Kay, 1996), we propose that, with development, [Ca 2ϩ ] c -dependent aequorin luminescence will prove to be a useful rhythmic marker phenotype in transgenic plants. In conjunction with the use of tissue or cell specific promoters to target the expression of apoaequorin to different locations within the plant, and topogenic sequences to direct expression to specific subcellular locations, this approach will facilitate the continuing investigations into both the role of Ca 2ϩ in circadian rhythmicities and the functional organization of the circadian clock mechanism in higher plants.…”
Section: Discussionmentioning
confidence: 99%
“…However in view of these data and the growing body of evidence that Ca 2ϩ plays an integral role in a number of rhythmic phenomena in plants (Neuhaus et al, 1993;Gomez and Simon, 1995;Anderson and Kay, 1996), we propose that, with development, [Ca 2ϩ ] c -dependent aequorin luminescence will prove to be a useful rhythmic marker phenotype in transgenic plants. In conjunction with the use of tissue or cell specific promoters to target the expression of apoaequorin to different locations within the plant, and topogenic sequences to direct expression to specific subcellular locations, this approach will facilitate the continuing investigations into both the role of Ca 2ϩ in circadian rhythmicities and the functional organization of the circadian clock mechanism in higher plants.…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude of the Ca 2ϩ increase in the cytosol after the Ca 2ϩ bolus in the stroma is not large (estimated to be 300 to 400 nM, increasing from a basal level of 150 to 200 nM), but locally (especially in cytosol near the chloroplast envelope), this Ca 2ϩ increase could be significant. There is abundant evidence for a role of Ca 2ϩ fluxes in the entrainment of circadian rhythms in animals (Ding et al, 1994;Geusz and Block, 1994;Colwell, 2000), and there is some evidence in plants as well (Gomez and Simon, 1994;Johnson et al, 1995). In some studies, light has been sug- Representative traces are shown for measurements from 18 different samples for each treatment (two separate experiments with three DCMU treatments at 2 M, three DCMU treatments at 10 M, and three medium treatments in each experiment).…”
Section: Potential Regulatory Consequences Of the Ca 2ϩ Burstmentioning
confidence: 99%
“…One of the most important of these stimuli that relates to the plant's response to its environment is the increase of cytosolic Ca 2 ϩ elicited by light/ dark signals (Shacklock et al, 1992;Millar et al, 1994). Light-induced Ca 2 ϩ fluxes have been implicated in the entrainment of circadian oscillators in plants (Gomez and Simon, 1994), and there are circadian oscillations of cytosolic Ca 2 ϩ (and possibly of chloroplastidic Ca 2 ϩ ) in tobacco and Arabidopsis (Johnson et al, 1995). Ca 2 ϩ is a regulator of myriad processes in all organisms, including plants, in which a number of Ca 2 ϩ -modulated proteins have been characterized, including calmodulin and a class of Ca 2 ϩ -dependent but calmodulin-independent protein kinases called calciumdependent protein kinases that are found in plants and some protozoa but are absent from animals and fungi (Roberts and Harmon, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…However, longer-term [Ca 21 ] cyt oscillations, characterized by a period of 24 h, occur in the cytosol and chloroplast of Nicotiana plumbaginifolia, in the cytosol of Arabidopsis (Arabidopsis thaliana; Johnson et al, 1995), and in the cytosol of neurons of the mouse suprachiasmatic nucleus, which is the primary circadian pacemaker in mammals (Ikeda et al, 2003). These circadian rhythms of [Ca 21 ] cyt are believed to be involved in signaling to or from the endogenous circadian clock (Gó mez and Simó n, 1995;Trewavas, 1999;Webb, 2003), although their precise role remains unclear (Sai and Johnson, 1999). One possibility is that circadian oscillations of [Ca 21 ] cyt encode information in a manner analogous to the short-period oscillations of [Ca 21 ] cyt induced by extracellular signals.…”
Section: Introductionmentioning
confidence: 99%
“…In plants, the circadian clock controls fundamental aspects of plant physiology and development, including gene expression (Harmer et al, 2000) and the movements of stomata (Webb, 1998(Webb, , 2003 and leaves (Gó mez and Simó n, 1995). The circadian clock is also the internal chronometer by which photoperiodic or daylength sensitive responses, such as seasonal growth, the induction and breaking of bud dormancy, vegetative reproduction, and floral development, can occur (Yanovsky and Kay, 2002;Hayama and Coupland, 2003).…”
Section: Introductionmentioning
confidence: 99%